Objective measures of physical performance associated with depression and/or anxiety in midlife Singaporean women - Ganasarajah, Shamini (LIPPINCOTT WILLIAMS & WILKINS, 2021)
MENOPAUSE-THE JOURNAL OF THE NORTH AMERICAN MENOPAUSE SOCIETY